Elementary teachers’ perceptions of science teaching constraints and affordances and their influence on science teaching self-efficacy and beliefs - Swanson, Russell W. (Kansas State University, 2023)
This study aimed to explore possible correlations between elementary inservice teachers’ (n=138) perceptions of science teaching constraints and affordances as well as their demographic information and science teaching self-efficacy and beliefs through the use of inferential statistics (Field, 2018; Riggs & Enochs, 1990). It also sought to explore teachers’ perceptions of events and policies and the effects they had on their science instruction, including the impact of COVID-19 responses through open-ended survey questions and qualitative data analysis (Saldaña, 2021). Due to philosophical, material, and logistical constraints placed on elementary teachers, science instruction is often limited in the elementary grade levels (Banilower, 2019; Banilower et al., 2018; Smith, 2020). Upon entrance into elementary classrooms, teachers often feel ill equipped to address the standards for a variety of reasons (Zinger et al., 2020). Reports have shown that these constraints and affordances placed on teachers have increased since the onset of the COVID-19 pandemic (Berger et al., 2022). This online survey research used a modified tailored-design method distributed to inservice elementary teachers through public elementary school principal contact information in a state in the Midwest (Dillman et al., 2014). This mixed-method, non-experimental exploratory research analyzed inservice elementary teachers’ perceptions of their own science teaching constraints and affordances along with their science teaching self-efficacy and beliefs through the STEBI-A to explore possible correlations between the two (Riggs & Enochs, 1990). The science teaching constraints and affordances used in this research include the amount of time elementary teachers have to teach science, their district and school lesson planning initiatives, the depth of the Next Generation Science Standards (NGSS), the physical materials they have access to, their adopted science curriculum, the facilities they have access to, their perceptions of professional development, and their perceptions of their Professional Learning Community (PLC). Secondarily, this research explored correlations between demographic information reported by teachers and the components of the STEBI-A. Lastly, open-ended written response items were also included to explore how teachers to describe how certain events or policies, including responses to the COVID-19 pandemic, have impacted their science instruction. For the quantitative analysis, exploratory MANOVA were used in analyzing the survey data to isolate correlations between both Science Teaching Outcome Expectancy (STOE) and Personal Science Teaching Self-Efficacy (PSTE) as they relate to science teaching constraints and affordances as well as demographic variables (Field, 2018). For the qualitative response analysis, two cycles of coding written responses were used in showcasing patterns and themes in the teachers’ experiences of both general events and policy changes as well as those related specifically to COVID-19 (Saldaña, 2021). Relationships between science teaching constraints and affordances and elementary inservice teachers’ STOE and PSTE were shown in the research, including relationships with teachers’ perceptions of the NGSS, physical materials, adopted curriculum, professional development, and PLCs as well as their experience in the classroom and type of curriculum. In the qualitative analysis, themes about time, materials, professional development, and other factors were shown to be a result of the results of general school and district policy as well as COVID-19 policy. Discussions of the results include applications for teacher inservice, elementary school building scheduling and initiatives, facilities, materials, curriculum, as well as general teacher support.
Keywords: Elementary science; Constraints and affordances; Science teaching self-efficacy; MANOVA; Science teaching efficacy and beliefs; Science teaching efficacy and beliefs instrument